Research of Operational Properties of Modified Specialized Concrete for Transport Constructions - Oleksandr Pshinko; Andrii Shcherbak; Dmytro Rudenko (Communications - Scientific letters of the University of Zilina, 2019)
It was established that the polymeric component of the organomineral modifying complex changes the nature of the super-molecular structures in the activated cement system - at optimal filling, globules decrease in size preventing the phase surface diffusion, which contributes to increase of the waterproofness of modified concrete. When introducing a modified cement system into the concrete mixture, the reduction of the open porosity to 3-5%, depending on the composition, has been achieved. Conducted tests for water resistance and frost resistance of the repair layer of concrete showed that the modified concrete corresponds to the mark on water resistance W14 and the brand on the frost resistance F300. The developed technology of physico-chemical activation of the cement system allows the use of conventional cement for obtaining durable concrete of special purpose, which allows to reduce the cost of such concrete by 27-34%.